1977
DOI: 10.1007/bf01488622
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcifications under maintenance hemodialysis

Abstract: In a cross-sectional study X-rays of the forefoot and the pelvis of 101 adult dialysis patients were taken. Vascular calcifications (forefoot) were observed in 20 patients. The incidence was higher in patients who had been started on dialysis several years ago. However, in a longitudinal prospective study de novo appearance of vascular calcificaitons was observed only in 1 out of 50 dialysed patients, although hyperparathyreoidism and moderate hyperphosphatemia persisted. Vascular calcifications were seen only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
1
5
0
3
Order By: Relevance
“…Furthermore, in agreement with previous reports we found that vascular calcifications are uncommon in uraemic children [21].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in agreement with previous reports we found that vascular calcifications are uncommon in uraemic children [21].…”
Section: Resultssupporting
confidence: 93%
“…Deposition of calcium salts in a variety of tissues has been found. In uraemic children extraosseous calcium deposits are soldom reported but autopsy data suggest that the prevalence may be much greater than commonly appreciated [21].…”
Section: Introductionmentioning
confidence: 97%
“…Arterial calcifications are frequent in dialysis patients [27,28], but they have sel dom been described to cause vascular insufficiency [29][30][31]. Granted that observations in our experimental model may not be relevant to man, it cannot be excluded that aggrava tion of arterial calcifications may be a hitherto unrecognized hazard of treatment with la-OH-D3 in uremic patients.…”
Section: Discussionmentioning
confidence: 67%
“…In the human situation, arterial calcifica tions arc frequently observed in chronic renal failure [84,85] similarly to what has been described in uremic rats [82], This anomaly could be in part attributed to a disturbed Caphosphate metabolism. However, it has been reported that the arterial lesions consist of calcified structures encountered in areas of the arterial walls with severe degenerative alterations (i.e., cell damage), not of diffuse calcifications of the ground substance [86], These lesions were not associated with the accumulation of lipids and differed thus from those observed in common atherosclerosis.…”
mentioning
confidence: 59%